Analisis Pengaruh Media Pembelajaran Digital Terhadap Prestasi Belajar Siswa Sekolah Dasar - Aura Permata Wihandarti; Ahmad Suriansyah; Wahdah Refia Rafianti (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Learning at the Elementary School (SD) level plays a very significant role as an initial foundation in formal education. Rapid developments in aspects of information and communication technology in the era of global progress have a significant impact on the achievement of learning objectives. One of the main targets of education is to optimize learning achievement. The purpose of this study is to analyze the influence of digital-based learning platforms on student learning achievement in elementary schools. In this modern era, information and communication technology brings important transformations in the world of education. Digital learning media, such as interactive applications and educational videos, have the potential to encourage student enthusiasm and participation in learning. Qualitative research uses a literature study method, which allows researchers to obtain information from various related literature. This study found that digital learning media can play a role in encouraging student achievement by improving the quality of learning and facilitating skills to understand concepts better. However, challenges such as gaps in technology access and lack of digital skills need to be addressed to maximize the effectiveness of using this media. This study suggests that educators and policy makers consider the use of digital media in the elementary education curriculum to improve the overall quality of learning.